2013
DOI: 10.1007/s00405-013-2812-6
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial comparing bismuth iodine paraffin paste external ear pack and no ear pack after middle ear surgery

Abstract: To pilot a substantive randomized control trial comparing post-operative external ear canal pack with no ear pack after middle ear surgery, 32 adults undergoing primary posterior bony canal wall preserving middle ear surgery were randomized to have either a bismuth iodoform paraffin paste pack or no ear pack post-operatively. Outcome measures included clinician- and patient-recorded visual analogue scale scores for ear signs and symptoms at 3 weeks and 3 months and audiometric findings at 3 months post-operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Similarly, chloramphenicol and wick packing [11] were not inferior options in cholesteatoma surgery. Fisal Et.al [9]had similar outcomes with BIPP packing and no packing and just overlaying absorbable Spongostan over the tympanomeatal ap in a cohort of middle ear surgeries. With regards to myringoplasty, Triadcortyl packing was found to have similar outcomes to BIPP [12] and a literature review by Ashraf and Capper[8] found no signi cant difference between different dressing types in myringoplasty success via the microscopic route.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, chloramphenicol and wick packing [11] were not inferior options in cholesteatoma surgery. Fisal Et.al [9]had similar outcomes with BIPP packing and no packing and just overlaying absorbable Spongostan over the tympanomeatal ap in a cohort of middle ear surgeries. With regards to myringoplasty, Triadcortyl packing was found to have similar outcomes to BIPP [12] and a literature review by Ashraf and Capper[8] found no signi cant difference between different dressing types in myringoplasty success via the microscopic route.…”
Section: Discussionmentioning
confidence: 85%
“…It is noted that there is little evidence with regards to the optimal timing of removal of the external ear canal dressing post-operatively [13] but upon review of the methods of relevant ear surgery papers [9]- [11], [25], leaving non-absorbable external ear canal dressing for more than three to four weeks is not commonplace in other centres. In keeping with common practice, we chose to remove Silastic splints at the 2 weeks, but we chose to keep the Spongostan in for three months due to its absorbable nature.…”
Section: Discussionmentioning
confidence: 99%
“…There were a few challenges during this study. The initial study protocol adjusted the required sample size based on an anticipated conservative dropout rate of 15% and incomplete questionnaire rate of 9% . However, the larger than anticipated dropout rate of 20% and SADL questionnaire partial completion rate of 30% limited the number of participant questionnaires that were available for interim in-study data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To discern a standardized difference of 0.63 (0.50/0.80) at a 5% significance level with a power of 80%, a total sample size of 80 participants was required based on the sample size nomogram by Altman . A conservative dropout rate of 15% that was related to failure to keep follow-up appointments or study withdrawals was adopted based on the senior authors’ experience in randomized clinical trials of more invasive interventions in which dropout rates ranged from 15.6% to 21.9% . Additionally, Hosford-Dunn and Halpern found that 9% of returned questionnaires were incomplete or contained errors and could not be used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation